An imperative approach for fluorosis mitigation: Amending aqueous calcium to suppress hydroxyapatite dissolution in defluoridation - Sankannavar, Ravi; Chaudhari, Sanjeev (Journal of environmental management, 2019)
Drinking of fluoride (F−) contaminated water causes fluorosis and thus providing safe drinking water to the affected community remains a major challenge. Therefore, defluoridation without disturbing water quality is imperative. Hydroxyapatite (HAP) is proved to have a potential application for defluoridation; however, its dissolution during defluoridation is a concern for its implementation. Experiments conducted by suspending HAP in F− solution and deionized water without F− show that former had high residual pH and PO43− than the latter with Ca2+ being absent in the former. This indicates that Ca2+ had participated in defluoridation and promoted HAP dissolution when Ca2+ was unavailable. Hence, HAP dissolution seems to be a governing step for defluoridation. However, higher residual PO43− and pH affect drinking water quality, and its usage may pose additional health problems. Thus, Ca2+ deficient defluoridated water is unfit for drinking unless it is treated further. Hence, the present work proposes a novel method to overcome HAP dissolution by amending aqueous Ca2+ to F− water. The results show that amending Ca2+ efficiently prevents HAP dissolution and enhances defluoridation capacity as an added feature. Furthermore, speciation using MINEQL+ and FTIR of fluoride-calcium treated HAPs suggest the possibility of defluoridation by aqueous CaF+ adsorption onto HAP besides F− ion exchange with OH−. [Display omitted] •HAP dissolution in defluoridation makes the treated water unfit for drinking.•Amending aqueous Ca2+ to F− water suppressed the HAP dissolution in defluoridation.•Aqueous Ca2+ amendment to F−-water provides Ca2+-enriched alkaline drinking-water.•Amending aqueous Ca2+ showed enhanced defluoridation capacity for HAP.•Deflouridation occurred by adsorption of aqueous CaF+ and ion-exchange.